Bringing a Fourth Order Autonomous Inverter Power Network into Such of a Second Order in a Normalized Form - Popov, Evgeniy I.; Hinov, Nikolay L. (Elektronika ir Elektrotechnika, 2016)
A method is developed for reducing the power inverter electricalcircuit of fourth order to an electrical network of second order. The reduction is based on the assumption that the output inverter voltage is practically with a sine-waveshape. The normalized form guarantees versatility of the investigation and independency in relation to the concrete inverter parameters like output power, supplying voltage and operating frequency. From the whole power network of fourth order two sub circuits are outlined: the output(load) sub circuit and the inverter commutating sub circuit. Both of sub circuits of a second order define the parameters of the endmost inverter circuit of the same order and consequently the mode of operation and parameters of the power inverter itself. The transformation is possible owing to the fact that the frequency dependencies of the output (load) sub circuit can be separated from the dependencies that describe the structural relationships between the two sub circuits. The results from that conversion are more accurate when the resonant frequencies of the both sub circuits and the operating frequency do not differ substantially. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.5879